2003
DOI: 10.1007/s00792-002-0297-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of fusion proteins containing SecY and SecE, components of the protein translocation complex from the halophilic archaeon Haloferax volcanii

Abstract: By exploiting the salt-insensitive interaction of the cellulose-binding domain (CBD) of the Clostridium thermocellum cellulosome with cellulose, purification of CBD-fused versions of SecY and SecE, components of the translocation apparatus of the halophilic archaeon Haloferax volcanii, was undertaken. Following transformation of Haloferax volcanii cells with CBD-SecY- or -SecE-encoding plasmids, cellulose-based purification led to the capture of stably expressed, membrane-bound 68 and 25 kDa proteins, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…Recent examples are the usage of the BgaH reporter enzyme for the in vivo analysis of constitutive and regulated promoters, and the development of methods for gene inactivation (Gregor & Pfeifer, 2005;Allers et al, 2004). A second possibility is to find a mesohalic protein that is salt-tolerant, and a recent example is the application of a bacterial cellulose-binding domain for affinity purification of fusion proteins and protein complexes from haloarchaea (Irihimovitch et al, 2003). A third possibility is to modify a mesohalic protein until it can withstand high salt conditions; a recent example is the application of a modified GFP for the in vivo analysis of proteasome function (Reuter & Maupin-Furlow, 2004).…”
Section: 'Halophilic Adaptation' Of Methodologiesmentioning
confidence: 99%
“…Recent examples are the usage of the BgaH reporter enzyme for the in vivo analysis of constitutive and regulated promoters, and the development of methods for gene inactivation (Gregor & Pfeifer, 2005;Allers et al, 2004). A second possibility is to find a mesohalic protein that is salt-tolerant, and a recent example is the application of a bacterial cellulose-binding domain for affinity purification of fusion proteins and protein complexes from haloarchaea (Irihimovitch et al, 2003). A third possibility is to modify a mesohalic protein until it can withstand high salt conditions; a recent example is the application of a modified GFP for the in vivo analysis of proteasome function (Reuter & Maupin-Furlow, 2004).…”
Section: 'Halophilic Adaptation' Of Methodologiesmentioning
confidence: 99%
“…Earlier studies have shown these chimeras to be expressed stably and localized exclusively to the membranes of the transformed haloarchaeal cells. 43 In such IMVs, the presence of the CBD moiety, fused to the cytoplasmically facing N terminus of H. volcanii SecE and SecY, would be expected to present a steric hindrance to any ribosomal binding at sites incorporating the CBD-SecE or CBD-SecY chimeras.…”
Section: H Volcanii Ribosomes Bind To Protein Sites In the Membranementioning
confidence: 99%
“…This suggests that SP-CBD is first completely synthesized inside the cells and only then secreted across the plasma membrane into the growth medium. teolysis of heterologously expressed fusion proteins in H. volcanii (22,29,30). Subcellular fractionation of the SP-CBDexpressing cells revealed that the preprotein and its derived breakdown products were restricted to the cytoplasmic fraction (data not shown).…”
Section: Methodsmentioning
confidence: 96%